Study on vibro-acoustic characteristics of bamboo-based angklung instrument - Hamdan, Sinin; Rahman, Md Rezaur; Zainal Abidin, Ana Sakura; Musib, Ahmad Fauzi (College of Natural Resources, 2022)
The frequency (or pitch) content of bamboo angklung musical instruments was analyzed. The pitch of the rattle tubes was determined via a Pico oscilloscope recording both the time and frequency spectrum. Fast Fourier transform analysis identified the fundamentals and overtones of the individual tubes, which were compared with the calculated theoretical resonance frequency. The pitch, due to the coupling effects of two rattle tubes, slightly varied from the pitch of the individual rattle tubes. Although both rattle tubes (played simultaneously) displayed the fundamental frequencies in both tubes, the individual tubes played separately did not produce the exact frequency obtained from both tubes played simultaneously. The spectrum of both tubes produced sound output from the individual tube, which is shown by two prominent peaks, corresponding to the pitch of the individual tube. Although the long and short tube show an individual fundamental frequency of 528 Hz and 1095 Hz, respectively, for C5 tube (when played separately), the coupling of both tubes produced the first and second peaks (when played simultaneously) at 546 Hz and 1093 Hz. Due to the disparity of the fundamental frequency, the inner diameter and length of the tube was utilized for the theoretical resonance frequency calculation.